Biodegradation of Cetyltrimethylammonium Bromide (CTAB) and Methylparaben (MP) in Shampoo and Hair Dressing Salon Waste Utilizing Bacteria Extracted from Sewage Treatment Sludge - Onuche, P. U.; Okibe, F. G.; Ajibola, V. O.; Okonkwo, Ugochukwu Udonna; Babatunde, Ezekiel Tosin (Chemistry and Biochemistry: Research Progress Vol. 5, 2025)
Surfactants are amphipathic compounds consisting of both a hydrophobic region (alkyl chains of various lengths, e.g., alkyl phenyl ethers, alkyl benzenes, etc.) and a hydrophilic region (e.g., carboxyl, sulphate, sulphonates, phosphates, etc.). The present study investigated the biodegradation of Cetyltrimethylammonium bromide (CTAB) and Methyl paraben (MP) both in Shampoo and hair dressing salon waste, using bacteria isolated from Sewage treatment sludge. The biodegradation was carried out according to the OECD Guideline for ready biodegradability and was monitored by Standard Spectrophotometric methods. The results obtained indicated that these compounds were degraded biotically by simple bacteria identified using a Microgen Kit for bacteria characterization.: Bacillus cereus and Pseudomonas fluorescens degraded 98.3% of the initial CTAB level in the Standard CTAB solution on 13 days of incubation; Pseudomonas fluorescens and Actinobacillus hominis degraded 96.7% of the initial CTAB level on 10 days of incubation and 92.0% of the original MP on 13 days of incubation in the Shampoo solution; Pseudomonas aeurogonisa and Klebsiella planticola degraded 95.3% of the initial CTAB level on 5 days of incubation and 94.7% of the original MP level on 4 days of incubation in the washing solution; Pseudomonas aeuroginosa and Salmonella typhi were found present in the Inoculum control. In conclusion, the results of this study suggest that the bacteria obtained from the sewage sludge can be used as a cost-effective and environmentally friendly agent for the biodegradation of surfactants in sewage treatment processes. The study recommended that the identified bacteria be applied individually for the biodegradation of surfactants so as to compare their biodegradation capacity and rate.